Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have the DE


The general solution to the corresponding homogeneous equation is,


How do I find a particular solution $y_p(x)$ that fits with this?

share|cite|improve this question
Before we do this, please check whether you have the right DE. If you do, the solution of the homogeneous equation is not quite right. – André Nicolas Oct 15 '11 at 16:55
the solution of the homogeneous equation is ok – pedja Oct 15 '11 at 17:13
@pedja, you really believe $x\mapsto\mathrm e^{2x}$ solves the homogenous equation? Wow. – Did Oct 15 '11 at 17:42
@AndréNicolas You're right, the equation was $y''-4y'+4y=e^{2x}$ , not $y''+4y'+4y=e^{2x}$ . Sorry about that. – JaHei Oct 15 '11 at 18:07
up vote 1 down vote accepted

There's a method called "the method of undetermined coefficients" that deals with such equations. Normally, when you see $e^{2x}$ on the right-hand side you try $y_p = Ae^{2x}$, plug it in, then solve for $A$. However, since $2$ is a double root of the characteristic equation $r^2 - 4r + 4 = 0$, you have to try $y_p = Ax^2 e^{2x}$ instead. If you plug this in, and solve for $A$, you obtain $A = {1 \over 2}$ and therefore $y_p = {1 \over 2}x^2 e^{2x}$.

share|cite|improve this answer
Perfect, thank you. – JaHei Oct 15 '11 at 21:28

$y^{\prime \prime} -4y^{\prime} + 4y = e^{2x} \quad \Rightarrow \quad (D^2 - 4D + 4)y = e^{2x} \quad \Rightarrow$

$(D -2)^2y = e^{2x} \quad \Rightarrow \quad y = \frac{1}{(D - 2)^2}e^{2x} = e^{2x}\frac{1}{D^2}\cdot 1 = \frac{x^2}{2}e^{2x}$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.